Andorra.: Vom abgeschlossenen Hochgebirgsstaat zum internationalen Touristenzentrum - Rinschede, Gisbert (ERDKUNDE, 1977)
The Principality of Andorra, which for centuries had resisted all influences from the outside, has developed during the last 40 years into an international tourist centre as a result of its special political conditions. In 1970 the non local transient tourists represented 40%, the short-trip local tourists 50%, and the extended-stay vacationers10% of the total 2.8 million tourists. They are mostly shopping tourists who want to buy low cost articles of all kinds in tax-free Andorra. The economic expansion has been accompanied by a strong immigration, especially by Spanish workers. As a result, during the 20-year period 1955-75, the population increased from 6,189 to 26,558 inhabitants.